An investigation into the awareness of climate change issues and lean practices in a Greek power plant - Asproulis, Christos (2007)
The current paper aims to shed light in to the awareness of climate change issues and lean practices in a Greek Power Plant and how these two may interrelate. Awareness is measured with the use of especially designed questionnaires which were distributed to a number of employees within the power plant from various areas of the business, from different positions and from different levels of academic education as well as different academic backgrounds. The paper contains a significant amount of quantitative analysis performed on the actual responses in order to draw valid and accurate conclusion regarding the level of the measured awareness on the two aforementioned issues.